Model pengurusan bakat dan prestasi organisasi di Bank Simpanan Nasional - Yong Salmah, Nasir (2019)
This study investigates the relationship between talent management, transformational leadership style and organizational performance. Talent management includes attraction, development, motivation, retention and succession planning. A research framework was developed, and two main hypotheses were posited and tested. The study was based on a survey design and cross sectional. A total of 300 questionnaires were collected from the management staff of Bank Simpanan Nasional (BSN) all over Malaysia, and were used in subsequent statistical analysis. Organisation of BSN as a unit analysis and all management staff around Malaysia were selected by using simple random sampling method. All hypotheses were tested using SPSS 24 – (Statistical Package for the Social Sciences). The results support all the hypotheses posited for the study, suggesting that talent management can influence organizational performance. Pearson correlation indicates that, all of the talent management practices have significant correlation with transformational leadership style and performance variables. Result of correlation shows that a set of talent management, transformational leadership style and organizational performance have significant correlation with each other. The results of principle component analysis and hierarchical linear regression indicates significant relationship between talent management, transformational leadership style, and organizational performance. Finally, the test highlights the role of transformational leadership style as moderating variable the relationship between talent management and organizational performance. In conclusion, this study provided an insight and further understanding of the inter-relationship between talent management, transfromational leadership and organizational performance, and hence allowing practitioners to gain an indepth knowledge about the model of talent management on organizational performance for Bank Simpanan Nasional (BSN).